PETA DAN KARAKTERISTIK PEMIKIRAN TEOLOGI ULAMA KOTA PALEMBANG ABAD XXI (EL-FIKR: Jurnal Aqidah dan Filsafat Islam, 2022)
Globalization that occurred in Palembang City in the XXI century, motivated scholars to formulate and contextualize the theology of civilization in Palembang City. The contextualization is plural and has distinction. This article aims to identify, reveal, and analyze the maps and characteristics of the theological thought of Palembang City scholars in the 21st century. The method used is development research. To develop the theory, a quantitative approach is used. The data collection tools used are questionnaires, documentation studies, and interviews. The data analysis technique used is quantitative data analysis consisting of simple linear regression analysis, instrument test, hypothesis test. Based on the methodology it was found that there are two maps and characteristics of the theological thinking of Palembang City scholars, namely: theocentric theology which is concerned with matters that are metaphysical in nature and anthropocentric theology which is concerned with matters that are practical reflections on teachings Islam: The contextualization of civilizational theological thought takes the form of theoretical civilization in the form of ideas and experimental civilization in the form of objects, buildings, religious activities, and social interactions. Keywords: contextualization, theology of civilization, XXI century, Palembang scholars